Intracellular phosphorylation of glucose analogs via the phosphoenolpyruvate: mannose-phosphotransferase system in Streptococcus lactis. - Thompson, J (1985)
The bacterial phosphoenolpyruvate:sugar-phosphotransferase system (PTS) mediates the vectorial translocation and concomitant phosphorylation of sugars. The question arises of whether the PTS can also mediate the phosphorylation of intracellular sugars. To investigate this possibility in Streptococcus lactis 133, lactose derivatives have been prepared containing 14C-labeled 2-deoxy-glucose (2DG), 2-deoxy-2-fluoro-D-glucose (2FG), or alpha-methylglucoside as the aglycon substituent of the disaccharide. Two of the compounds, beta-O-D-galactopyranosyl-(1,4')-2'-deoxy-D-glucopyranose (2'D-lactose) and beta-O-D-galactopyranosyl-(1,4')-2'-deoxy-2'-fluoro-D-glucopyranose (2'F-lactose), were high-affinity substrates of the lactose-PTS. After translocation, the radiolabeled 2'F-lactose 6-phosphate (2'F-lactose-6P) and 2'D-lactose-6P derivatives were hydrolyzed by P-beta-galactoside-galactohydrolase to galactose-6P and either [14C]2FG or [14C]2DG, respectively. Thereafter, the glucose analogs appeared in the medium, but the rates of sugar exit from mannose-PTS-defective mutants were greater than those determined in the parent strain. Unexpectedly, the results of kinetic studies and quantitative analyses of intracellular products in S. lactis 133 showed that initially (and before exit) the glucose analogs existed primarily in phosphorylated form. Furthermore, the production of intracellular [14C]2FG-6P and [14C]2DG-6P (during uptake of the lactose analogs) continued when the possibility for reentry of [14C]2FG and 2DG was precluded by addition of mannose-PTS inhibitors (N-acetylglucosamine or N-acetylmannosamine) to the medium. By contrast, (i) only [14C]2DG, [14C]2FG, and trace amounts of [14C]2FG-6P were found in cells of a mannose-PTS-defective mutant, and (ii) only [14C]2FG and [14C]2DG were present in cells of a double mutant lacking both mannose-PTS and glucokinase activities. We conclude from these data that the mannose-PTS can effect the intracellular phosphorylation of glucose and its analogs in S. lactis 133.